Increased expression of the sodium/iodide symporter in papillary thyroid carcinomas. - Saito, T (1998)
Iodide is concentrated to a much lesser extent by papillary thyroid carcinoma as compared with the normal gland. The Na+/I- symporter (NIS) is primarily responsible for the uptake of iodide into thyroid cells. Our objective was to compare NIS mRNA and protein expression in papillary carcinomas with those in specimens with normal thyroid. Northern blot analysis revealed a 2.8-fold increase in the level of NIS mRNA in specimens with papillary carcinoma versus specimens with normal thyroid. Immunoblot analysis using anti-human NIS antibody that was produced with a glutathione S-transferase fusion protein containing NIS protein (amino acids 466-522) showed the NIS protein at 77 kD. The NIS protein level was elevated in 7 of 17 cases of papillary carcinoma but was not elevated in the normal thyroid. Immunohistochemical staining revealed abundant NIS in 8 of 12 carcinomas, whereas NIS protein was barely detected in specimens with normal thyroid. Although considerable patient-to-patient variation was observed, our results indicate that NIS mRNA is elevated, and its protein tends to be more abundant, in a subset of papillary thyroid carcinomas than in normal thyroid tissue.